The prisoners work in the prisons on the Belarusian lands at the end of the 19th – early 20th centuries - Chaikin, Sergey N. (Journal of the Belarusian State University. History, 2020)
The history of the development of the prisoners work on the Belarusian lands after the prison reform of 1879 is the object of examination. In the historiography of pre-revolutionary, Soviet and modern periods this problem has never been studied by neither Russian nor Belarusian scientists. The examination of the prisoners work development in the local prisons as well as the determination of its common patterns for the Belarusian lands and the Russian Empire in general, and of the regional characteristics of this process are the purpose of the research. The main ways of action of the General Directorate of the Corps of Prison on the labour productivity of the prisoners on Belarusian lands (organisation of its local structural subdivision (province prison inspections) which managed the prisoners work, the organisation of the melioration and logging, the development of work in the prisons workshops) are being examined by the author on the base of the study of the archive data. The core activity of the fulfilment in the local prisons at the end of the 19th – early 20th centuries and the negative phenomena which interrupt it (in general the overcrowding of the places of determination that influenced the closure of the workshops) are being determined. The results of the prisoners work development by the turn of the second decade of the 20th century which are the growing numbers of the working prisoners and the increase of their salary activity from the beginning of the 20th century are being appreciated. The undertaken research will make it possible to determine the historical continuity of the series of measures to develop the prisoners work in the places of detention at the end of the 19th – early 20th centuries with the activity of the manufacturing establishments of the penitentiary system of the Republic of Belarus at the present time.
Keywords: the Russian Empire; the Belarusian lands; the prison reform of 1879; the General Directorate of the Corps of Prison; province prison inspection; the prisoners works; the prison workshops